2016
DOI: 10.5209/cuts.51126
|View full text |Cite
|
Sign up to set email alerts
|

Tipologías actuales de los trabajadores sociales en España

Abstract: IntroducciónEl desempeño profesional de los profesionales del Trabajo Social en España es cada vez más heterogéneo y diversificado, como producto de la mayor complejidad, pluralidad y diversidad de las problemáticas a las que debe hacer frente la profesión. Esta es una representación colectiva bastante extendida, donde parece imperar la ló-gica de la fragmentación, donde la profesión parece difuminarse en una infinidad de particularidades. En esta línea, Hernández (2004, p. 176 Resumen El objetivo del artículo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
1
5
0
5
Order By: Relevance
“…Table 1 shows the socio-demographic characteristics of the study sample. The results obtained indicate that the study sample is similar to that of the general population of social workers in Spain, in terms of the variables of gender, age and professional experience, according to reports by Viscarret, Ballestero, Idareta and Uriz (2016). All the participants were volunteers and gave their informed consent.…”
Section: Samplesupporting
confidence: 62%
“…Table 1 shows the socio-demographic characteristics of the study sample. The results obtained indicate that the study sample is similar to that of the general population of social workers in Spain, in terms of the variables of gender, age and professional experience, according to reports by Viscarret, Ballestero, Idareta and Uriz (2016). All the participants were volunteers and gave their informed consent.…”
Section: Samplesupporting
confidence: 62%
“…One of the main concerns of social workers in Spain is the bureaucratization of social work and care work (Hidalgo-Lavié & Lima-Fernández, 2018;Viscarret, Ballestero, Idareta, & Úriz, 2016). Social workers, who are in charge of implementing social care, face a double mandate.…”
Section: Challenges Of Digitalization In Care and Social Servicesmentioning
confidence: 99%
“…On one hand, they must display the essence of direct social intervention, defending citizens' rights. On the other hand, they must implement governmental mandates using the bureaucratic systems in place (Viscarret et al, 2016). According to Lipsky (1980), this is understood as a final level in policy-making, where public servants (social workers, in this case) have to make decisions quickly and in a way that will be understandable to citizens.…”
Section: Challenges Of Digitalization In Care and Social Servicesmentioning
confidence: 99%
“…When analysing the academic literature, it is notable how often academics and professionals who study the field refer to social work professionals as females. In a national study, it was found that 91 per cent of professionals are women and only 9 per cent are men (Viscarret, Ballestero, Idareta and Úriz, 2016).…”
Section: From Social Assistance To Social Workmentioning
confidence: 99%